On tests for long-term dependence: India ’s international tourism market - Chaitip, Prasert; Balogh, Péter; Kovács , Sándor; Chaiboonsri, Chukiat (Applied Studies in Agribusiness and Commerce, 2011)
There have been growing interest in studying behavior of long memory process in tourism market. In this research examine the behavior of India’s international tourism market based on long-memory analysis. The international tourism market of India combined with nine countries: USA, UK, Canada, Germany, France, Japan, Malaysia, Australia and Sri Lanka. Moreover, three statistical tests for longmemory process such as R/S test, Modified R/S test and GPH-test are employed to test in these market. The empirical findings in general provide more support for no long memory process or no long-term dependence in international tourism market of India.